EXPERIMENTAL STUDY AND ANALYSIS ON THE EFFECT OF M40 CONCRETE ON THE DURABILITY STRENGTH PROPERTIES WITH PARTIAL REPLACEMENT OF SAND WITH COPPER SLAG - Oybek Oripov1*, Gavhar Narmayeva1, Jamoliddin Kuljonov1, Muqaddas Abdushukurova2 (Journals Park Publishing, 2023)
Today, rapid industrialization has led to an increase in the demand for housing. Due to its environmental impact, the use of plant sand for concrete production is limited. The shortage of lime and concrete for the production of high-quality aggregates was solved by the partial replacement of gravel with copper sulfide. The research paper reviews some experimental studies on the effect of copper sulphide as a partial replacement of sand on the performance of concrete. In this paper, an experimental study was conducted to investigate the effect of copper sulfide as a fine admixture on the accommodation of concrete. Copper slag is a by-product of copper production, which contains a large amount of iron oxide and silicate and is chemically stable. In this study, experimental work was carried out on M40 concrete for a comprehensive study. Several concrete samples were prepared by modifying the satisfactory mix with copper sulfides varying from 0% to 100% in specific proportions at intervals of 20% (0%, 20%, 40%, 60%, 80% and 100%). The effect of acids such as (H2 SO4 and HCl) and the effect of sulfates such as (Na2 SO4, and MgSO4) on hardened concrete samples affect the hardened concrete samples and the variation in weight loss and compressive strength is determined. According to the results of the investigation, the best ratio of using copper sulfide for fine aggregate in concrete is optimized and the results obtained are compared with the version between the concrete samples replaced with ordinary Portland cement and sand and the compression results and the version with concrete weight. The test results show that copper sulfide can be used as a satisfactory aggregate in concrete.
Keywords: potassium sulfate; magnesium sulfate; concrete; copper slag; gas permeability; granular slag; M40 concrete.